2005
DOI: 10.1071/ea03097
|View full text |Cite
|
Sign up to set email alerts
|

The northern Australian beef industry, a snapshot. 2. Breeding herd performance and management

Abstract: Breeding herd performance and husbandry were surveyed on 375 northern Australian beef properties in 8 regions during 1996 and 1997. Mean branding rates ranged from 62.6% in the Northern Territory to 77.1% in the Maranoa South West regions of Queensland with considerable variation within regional herds. The proportion of herds using controlled mating was highest in the Central Coastal, Central Highlands and Maranoa South West. Mean mating period across all regions varied from 5.6 to 11.8 months. Calving was sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 32 publications
3
54
0
1
Order By: Relevance
“…However, in northern Australia this is further exacerbated by poor conception and weaning rates compared with cattle in the temperate regions of southern Australia. Bortolussi et al (2005) surveyed segments of the northern industry in the 1990s and found weaning rates varied between 50 and 80%. When this is coupled with low weaning weights of <0.3 of the maternal weight, it is clear that there is major scope for improvement in both weaning rate and weight.…”
Section: The Extensive Cattle Industrymentioning
confidence: 99%
“…However, in northern Australia this is further exacerbated by poor conception and weaning rates compared with cattle in the temperate regions of southern Australia. Bortolussi et al (2005) surveyed segments of the northern industry in the 1990s and found weaning rates varied between 50 and 80%. When this is coupled with low weaning weights of <0.3 of the maternal weight, it is clear that there is major scope for improvement in both weaning rate and weight.…”
Section: The Extensive Cattle Industrymentioning
confidence: 99%
“…In northern Australia, protein supplementation of breeder herds is necessary to maintain body condition during the dry season (Bortolussi et al 2005), while in Southern Australia, breeder cattle often graze winter and spring pastures that provide greater than the recommended level of protein (Walsh & Birrell 1987). We have previously reported that male fetuses exposed to a low level of maternal nutrient intake during the first trimester were heavier throughout the postweaning period compared with their high-nutrient exposed counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising given the high rate of foetal growth during this period compared to the first and third trimesters (Eley et al, 1978). Due to seasonal rainfall patterns and therefore pasture quality (Norman, 1963, Robinson and Sageman, 1967, Holroyd et al, 1977, McIvor, 1981, Squires and Siebert, 1983, Coates, 2000 and herd management across northern Australia (Bortolussi et al, 2005), many breeding herds are likely experiencing decreasing pasture quality as their pregnancies progress. Therefore, many breeding herds may be at high risk of nutritional deficiency during mid-and especially late-gestation and consequently at risk of producing low birth weight calves.…”
Section: Calf Ability To Sucklementioning
confidence: 99%
“…Therefore the majority of cows in northern Australia are experiencing dry season conditions and low quality pasture during mid-late gestation. Consequently, the majority of calves in northern Australia are born between the months of October and January, with a tendency for later peak of calving further north (Bortolussi et al, 2005).…”
Section: General Risk Factors Influencing Calf Survivalmentioning
confidence: 99%